ANALISIS RESPONSIVITAS KETAATAN EMITEN TERHADAP ATURAN BOARD GOVERNANCE: STUDI KASUS PERUSAHAAN DI BURSA EFEK JAKARTA - Nuryanah, Siti (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
This study is to analyze the responsiveness of companies’ compliance with the regulation of board governance structure, authorized by Jakarta Stock Exchange (JSX). The study observes all companies that were listed in JSX in 2002. The objectives of this study are to describe the differences of the compliance responsiveness and to examine whether the asset’s size, the age of emiten listed in JSX, and the industries are the explanatory variables of the board governance structure. The study finds that the responsiveness of listed companies’ compliance categorized by the industries is significantly different. The study also finds that the responsiveness of listed companies’ compliance categorized by the asset’s size and the age of emiten listed in JSX is not significantly different. The listed companies in the banking and financial sector industry are more responsive to comply with the board governance regulation than the other listed companies in the other industries. The result of the study is consistent with some empirical studies finding that the companies’ board governance structure is because of industry factor.